Analyzing the Digital Divide in Egypt - Mohamed, Samah Abd El- Monem Fahmy (The Arab Journal of Administration, 2025)
The field of information and communication technologies (ICT) will play a central role in society, especially after the spread of global epidemics. It is, therefore, more important than ever to address the obstacles that prevent the penetration of this area in different aspects of society. The study aimed to understand and analyze the digital divide in Egypt through the ICT Development Index issued by the International Telecommunication Union, through three main dimensions: ICT access; ICT Use; and ICT skills. The results showed that women had a higher digital divide than men, and there was a gap between rural and urban areas whether in terms of access or use. In addition, there is a digital divide between Egypt and the countries of the world in indicators of use and skills, not access. This means that Egypt has been able to build a strong ICT infrastructure that has helped it achieves almost universal penetration rates and even outperformed it in some access indicators. This means that the digital divide in Egypt is not due to the physical lack of availability of devices, technology, and the internet, but has other dimensions, including economic, social, educational, and cultural.